China Satellite Navigation Conference (CSNC) 2016 Proceedings: Volume III - Sun, Jiadong; Liu, Jingnan; Fan, Shiwei; Wang, Feixue; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2016)
These Proceedings present selected research papers from CSNC2016, held during 18th-20th May in Changsha, China. The theme of CSNC2016 is Smart Sensing, Smart Perception. These papers discuss the technologies and applications of the Global Navigation Satellite System (GNSS), and the latest progress made in the China BeiDou System (BDS) especially. They are divided into 12 topics to match the corresponding sessions in CSNC2016, which broadly covered key topics in GNSS. Readers can learn about the BDS and keep abreast of the latest advances in GNSS techniques and applications. .
Satellite Orbit and Clock Offset Determination -- BDS/GNSS Precise Positioning Technology -- Atomic Clock and Time-frequency Technology -- Standardization, Intellectual Properties, Policies, and Regulations.
Keywords: Aerospace engineering; Astronautics; Telecommunication; Geographic information systems; Geophysics; Aerospace Technology and Astronautics; Communications Engineering, Networks; Geographical Information System; Geophysics